The analysis of scientific literacy skills in grade VII students in learning science biology - Ratih Monika Nasution; Ika Chastanti (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2023)
Scientific literacy is the skill and ability to write and read, conclude a lesson learned, explain phenomena around us, and identify a question. This research aims to analyze the scientific literacy abilities of class VII students in science teaching at SMP Negeri 4 Kampung Rakyat. The research method used is descriptive qualitative. The sample for this research was 30 students and three teachers at SMP Negeri 4 Kampung Rakyat. The population in this research is all students and teachers. Data collection techniques include questionnaires, observation, and interviews. The research results show that students who could solve questions based on scientific phenomena obtained a percentage of 89.48% in the first indicator. In contrast, in the second indicator, students who could understand and draw conclusions received 54.34%. In the third indicator, students who could explain their knowledge of scientific literacy results were 57.19%. The decision is that students' scientific literacy abilities in solving problems based on phenomena are already high. In contrast, the indicators for drawing conclusions and explaining knowledge still need to be improved. This study can be a basis for further research focusing on learning innovation to improve indicators that are still need to enhancing.Abstrak Literasi sains adalah suatu keahlian dan kemampuan dalam menulis maupun membaca, menarik suatu kesimpulan dalam suatu pembelajaran yang dipelajari, mampu menjelaskan fenomena yang ada di sekitar, dan dapat mengindentifikasi suatu pertanyaan. Penelitian ini bertujuan untuk menganalisis kemampuan literasi sains pada peserta didik kelas VII dalam Pembelajaran IPA di SMP Negeri 4 Kampung rakyat. Metode penelitian yang digunakan adalah kualitatif deskriptif. Sampel penelitian ini adalah 30 peserta didik dan tiga guru di SMP Negeri 4 Kampung rakyat. Populasi dalam penelitian ini adalah adalah seluruh peserta didik dan guru. Teknik pengumpulan data meliputi angket, observasi dan wawancara. Hasil penelitian menunjukkan pada indikator pertama peserta didik yang mampu menyelesaikan soal berdasarkan fenomena ilmiah memperoleh hasil persentase 89.48%. Sebaliknya, pada indikataor kedua peserta didik yang dapat memahami dan memberikan penarikan kesimpulan memperoleh hasil persentase 54.34%, dan pada indikator ketiga peserta didik yang mampu menjelaskan pengetahuan literasi sains memperoleh hasil persentase 57.19%. Kesimpulannya adalah kemampuan literasi sains peserta didik dalam menyelesaikan soal berdasarkan fenomena sudah tinggi. Sebaliknya, indikator menarik kesimpulan dan menjelaskan pengetahuan masih perlu ditingkatkan. Studi ini dapat menjadi dasar untuk penelitian selanjutnya dalam memfokuskan inovasi pembelajaran untuk meningkatkan indikator yang masih perlu ditingkatkan.